Temporal analysis of rainfall changes in Bardarash district using CHIRPS data between 1982 and - خياط, ا.م.د. هونر عبد الله خياط; حمۆ, سعد هادی حمو (Sulaimani Journal for Humanities, 2025)
Rainfall is a fundamental component of the climate system, playing a critical role in agricultural productivity, water resource management, and ecosystem sustainability. This study focuses on analyzing the spatial and temporal variability of rainfall in the Bardarash district, utilizing Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS) over 43 years (1981–2023). The primary aim of the research is to examine seasonal and annual precipitation trends, their spatial distribution, and their implications for drought conditions in the region. By analyzing long-term precipitation patterns, the study offers insights into the potential impacts of climate change on rainfall characteristics and drought dynamics. Our findings reveal that CHIRPS data provide comprehensive spatial coverage, especially beneficial in areas lacking dense ground-based meteorological stations. Each CHIRPS grid cell covers approximately 4.5 x 5.5 km², allowing for detailed spatial analysis. The Bardarash district, which has only one meteorological station with incomplete and sporadic historical data, greatly benefits from CHIRPS as a reliable alternative data source. Over the study period, rainfall exhibited notable interannual variability. For instance, the highest recorded annual precipitation occurred in 2019 with 1,234.3 mm, while the lowest was in 2008 with only 357.8 mm. Other low-precipitation years include 1989 (363.5 mm) and 2012 (377 mm). The standard deviation of annual precipitation during the study period was 153.5 mm, highlighting significant fluctuations across the years. Spatially, rainfall distribution was not uniform across the study area. Precipitation generally increased toward the north and northeast, while the southern and southwestern parts experienced lower rainfall levels. This spatial disparity was captured through the generation of isohyet maps using 48 sampling points across the district. These maps revealed that rainfall isolines were unevenly distributed, further emphasizing the region’s heterogeneous precipitation regime. Moreover, CHIRPS data facilitated both raster- and vector-based geospatial analyses, enabling the application of various statistical methods to assess rainfall variability across space and time. The ability to extract point-based and area-wide precipitation statistics allowed for a more accurate representation of rainfall distribution, making CHIRPS a robust and valuable tool for hydrological and climate studies in data-scarce regions. In conclusion, this study highlights the utility of satellite-derived CHIRPS precipitation data in understanding rainfall variability in the Bardarash district. The results underscore the crucial role of remote sensing in monitoring climate variability, particularly in regions with limited ground-based observational infrastructure.
Keywords: Spatial Analysis; Temporal Variation; Precipitation; CHIRPS; Bardarash